2009
DOI: 10.1258/acb.2009.009030
|View full text |Cite
|
Sign up to set email alerts
|

Serum total cortisol and free cortisol index give different information regarding the hypothalamus–pituitary–adrenal axis reserve in patients with liver impairment

Abstract: Background: The short synacthen test (SST) is used to investigate patients with suspected hypothalamus -pituitary-adrenal (HPA) axis pathology. A rise of serum total cortisol (total cortisol) above 550 nmol/L is accepted as sufficient adrenal reserve. In total, 80% of cortisol is bound to cortisol-binding globulin (CBG) and 10% to albumin. In the acute phase responses CBG concentrations decrease and can influence the interpretation of SST. The free cortisol index (FCI) is a surrogate marker for free cortisol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 12 publications
2
25
1
Order By: Relevance
“…In lieu of direct measurements, surrogate markers have been advocated, of which the Coolens equation and the Free Cortisol Index (FCI) are the most frequently described. The Coolens method has been found to provide values that correlated highly with measured PFC [21] and the FCI has been argued to be a better determinant of HPA-axis function than total cortisol [22]. In our study we found no significant correlation between the peak PFC and FCI.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In lieu of direct measurements, surrogate markers have been advocated, of which the Coolens equation and the Free Cortisol Index (FCI) are the most frequently described. The Coolens method has been found to provide values that correlated highly with measured PFC [21] and the FCI has been argued to be a better determinant of HPA-axis function than total cortisol [22]. In our study we found no significant correlation between the peak PFC and FCI.…”
Section: Discussioncontrasting
confidence: 64%
“…Evidence to support this hypothesis has come from studies in critically ill patients which have demonstrated a poor correlation between total and free cortisol estimations, and suggested that free cortisol fraction is more closely related to disease severity than is the total concentration [21,20]. A recent study examining 26 patients with liver impairment compared the Free Cortisol Index (FCI) with standard total cortisol diagnostic criteria and demonstrated that in 46% of patients there was a discrepancy between the two methods [22]. However, this method cannot account for the non-linear binding properties of CBG and thus the higher proportional increase in free cortisol following ACTH stimulation [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FCI was calculated as a ratio between total cortisol (nmol/L) and CBG (mg/L) [31]. cFC was derived using the Coolen' equation:…”
Section: Calculated Plasma Free Cortisolmentioning
confidence: 99%
“…Additionally, a separate analysis was performed using a cut-off value less than 16 lg/dl for peak total serum cortisol, recently proposed as a more sensitive cut-off [21], and a delta cortisol less than 9 lg/dl as suggestive of an inadequate adrenal response [9]. As previously described, FCI above 12 represented sufficient adrenal response [31].…”
Section: Definitionsmentioning
confidence: 99%